Deformasi Timbunan Underpass Km 41 + 00 Jalan Bypass Bill Mandalika - Muhammad Amrullah; Sukandi; I Gede Utama Hadi Sutrisna (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the slope stability and behavior of expansive clay soil at the underpass site located at KM 41+00 of the Bypass Mandalika road using a numerical simulation approach with PLAXIS 2D software. The study area is characterized by flat geomorphology with a slope inclination of less than 40.3Â° and surface geology consisting of expansive clay deposits from alluvium, which exhibit significant shrink-swell behavior due to moisture variation. A geotechnical investigation was conducted using hand auger drilling to a depth of 2 meters, followed by laboratory testing to determine physical and mechanical soil properties such as moisture content, specific gravity, cohesion, and internal friction angle. These parameters were then used as input data for the numerical modeling. Simulations were performed under two conditions: existing conditions and post-consolidation after four years under a 20-ton vehicular load. The results indicated that vertical deformation increased from 5.06 mm to 10.74 mm, while horizontal deformation rose from 7.05 mm to 15.46 mm. The slope safety factor improved from 1.39 to 1.59 after consolidation, indicating that the slope remains stable. However, periodic monitoring and potential slope reinforcement are recommended to ensure long-term stability, especially under conditions of heavy rainfall or high traffic loads.